BioKnit: development of mycelium paste for use with permanent textile formwork - Kaiser, Romy; Bridgens, Ben; Elsacker, Elise; Scott, Jane (Frontiers in Bioengineering and Biotechnology, 2023)
This paper presents significant advances in mycelium biofabrication using permanent knitted textile formwork and a new substrate formulation to dramatically improve the mechanical properties of mycelium-textile biocomposites suitable for large-scale components for use in construction. The paper outlines the biofabrication process, detailing the composition of mycocrete, a viscous mycelium substrate developed for use with permanent knitted formwork, and the injection process required to regulate the filling of slender tubes of fabric with mycocrete. The use of a permanent integrated knitted formwork shows promise as a composite system for use with mycelium to improve mechanical performance and enable complex shapes to be fabricated for lightweight construction. Results of mechanical testing show dramatic improvements in tensile, compressive and flexural strength and stiffness compared to conventional mycelium composites. The testing demonstrates the importance of both the mycocrete paste recipe and the knitted textile formwork. In addition, the paper highlights the advantages of the proposed biofabrication system with reference to the BioKnit prototype: a 1.8m high freestanding arched dome composed of very slender biohybrid knit-mycelium tubes. This prototype demonstrates the opportunity to utilize the potential for lightweight construction and complex form offered by a textile formwork with low environmental impact mycelium biomaterials. The combination of textiles and mycelium present a compelling new class of textile biohybrid composite materials for new applications within the construction sector.